Pregnancy in primary sclerosing cholangitis. Issue 8 (21st February 2011) - Wellge, Björn E; Sterneck, Martina; Teufel, Andreas; Rust, Christian; Franke, Andre; Schreiber, Stefan; Berg, Thomas; Günther, Rainer; Kreisel, Wolfgang; zu Eulenburg, Christine; Braun, Felix; Beuers, Ulrich; et al.
Abstract : Background: There is a paucity of data on fertility or pregnancy in patients with primary sclerosing cholangitis (PSC). Objective: To assess fertility in PSC by comparing the number of children in a large cohort of PSC patients to healthy controls and to investigate the outcome of pregnancy, as well as the influence of pregnancy on the disease course. Design: Case series. Setting: Germany. Participants: 229 PSC patients and 569 healthy controls were evaluated for the number of children. 17 patients with PSC and at least one pregnancy, or who received a diagnosis of PSC within 6 months after delivery, were included in the more detailed analysis. Main outcome measures: Number of children per patient and control; disease activity during pregnancy and after delivery including maternal complications; long-term development of live births, fetal loss rate and the influence of medication on fetal and maternal outcome. Results: Fertility did not seem to be reduced in PSC since the number of children did not differ between PSC patients and healthy controls. 25 pregnancies in 17 female PSC patients (median age at conception 31 years) were investigated in detail. An increase in liver enzymes was documented during five pregnancies (20%) and eight times (32%) post-partum. There were no serious maternal complications. All 21 live births presented with a normal perinatal and postnatal development over a median observation time of 50 months. Two pregnancies were delivered pre-term and four fetal losses occurred early in pregnancy (<12 wk). Continuation of treatment with ursodeoxycholic acid (15/21) or azathioprine (2/21) had no negative effects on pregnancy outcome. Conclusions: Fertility does not seem to be reduced in patients with PSC, who are able to deliver healthy children without an apparent increase in risk for mother or child.